FORMULATION OF PROPHETIC CHARACTERS AS THE BASE FOR ANTI-CORRUPTION EDUCATION IN UNIVERSITY - Nur Chanifah (Pusat MPK Universitas Brawijaya, 2021)
Formulation of Prophetic Characters as the Base for Anti-Corruption Education in University. This study aimed to formulate a prophetic character as a base for anti-corruption education so that it could provide some solutions in the development of anti-corruption education in university. Considering the effort to eradicate corruption through education is an inevitability in the midst of rampant corruption by a number of political elites. The method used was a literature review with data processing techniques including editing, classifying, and concluding. While the data analysis used content analysis with descriptive-qualitative data presentation type. The results showed that in relation to anti-corruption education in university, prophetic characters include four characteristics of the Prophet (Rasulullah), namely honest (shiddiq), trustworthy (amanah), communicative (tabligh), and intelligent (fathanah). These four characters are reflected in figures who always guide their conscience and truth, maintain professionalism and commitment, master communication skills with various groups and levels, and have the ability  solve any problem.